DESAIN KURIKULUM YANG FLEKSIBEL UNTUK ANAK BERKEBUTUHAN KHUSUS PADA TK PANGUDI LUHUR VINCENTIUS - Widoningrum, Wulandari Kusuma; Rahmawati, Dini; Handayani, Arri (Universitas Tanjungpura, 2025)
This research aims to design a flexible curriculum for children with special needs (ABK) at Pangudi Luhur Vincentius Kindergarten by taking into account the individual characteristics and potential development needs of each child. This research uses a qualitative approach and research and development methodology. Documentation studies, in-depth interviews, and observations are some of the methods used to obtain data. The urgency of this research lies in the urgent need to design a flexible curriculum that not only accommodates the diversity of children with special needs, but is also able to transform the educational paradigm from a standard model to a truly inclusive model, where each child is seen as having unique capacities that deserve to be developed optimally through intervention. personalized, adaptive and sustainable education. The interactive model is used to carry out descriptive-qualitative data analysis. Miles and Huberman. The research results show the need for adaptive curriculum design, which is able to accommodate the diversity of needs of ABK through modified learning strategies, individual assessments, and potential-based approaches. The resulting flexible curriculum design includes six main components: individual assessment, specific development targets, adaptive learning strategies, customized learning media, dynamic assessment systems, and ongoing mentoring.